New Multi-function Composite Device Researching in Micro-grid - Shengqing Li; Weizhou Li; Wenxiang Xu; Huanyue Zeng (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In the view of economic conditions to improve the Micro-grid quality, paper puts forward a new type multifunctional composite device. Combination the consistent characteristics of the main circuit structure from micro-grid energy storage battery and active power filter, combining the two components of multifunctional composite device, with corresponding control to achieve a variety of functions. This paper analyzes the working principle of the energy storage battery and active power filter, with the comparative analysis of its structural features, given the composite principle, derived the mathematical model of composite device, by containing harmonic suppression link power decoupled control method to achieve effective control. Simulation shows that the composite device effectively adjusting the active power and reactive power and harmonic suppression of Micro-grid, verify the rationality and validity of the composite device. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4735